Classe inversée en enseignement supérieur et dynamique d'élaboration du savoir : le point de vue des enseignants - Dorothée Baillet; Françoise Robin (Nantes Université, 2022)
Following the development of information technologies, higher education is evolving towards hybrid devices with the flipped classroom. This article reports on research that attempts to perceive differentiated repositioning of space-time and actors in the flipped classroom. We interviewed nine higher education teachers in Belgium (French-speaking part) who call themselves "inverters". The study of the reasons that led these teachers to opt for the flipped classroom system highlights the importance of personal experiences as well as the existence of differences in interactions with students. These results, coupled with the analysis of the implementation of the system through the didactic triplet (Sensevy, 2011), have brought to light two ideal-types. The first is characterized by the teacher's control over the entire system or the devolution of the advancement of knowledge to the students. The second alternates control and devolution.